Effect of Alloying Composition on Microstructure and Mechanical Properties of Ultranarrow Gap Welded Joints of U71Mn Rail Steel - Lian Gong; Hui Liu; Cheng Lv; Lijun Zhao (Advances in Materials Science and Engineering)
A new welding method, ultranarrow gap welding with constrained arc by flux band, is proposed to compensate for the low quality of rail thermite welded joints. This article presents the results of research on the microstructure and mechanical properties of ultranarrow gap welded joints of U71Mn rail steel made using three types of alloying composition content flux bands. Results indicated that the base metal metallographic microstructure consisted mainly of pearlitic, the HAZ was mainly composed of fine pearlite, and the microstructure of the welded bead was composed of acicular ferrite, while the weld grain size decreased as the alloy composition increased. The average hardness noticeably changed in weld metal as the alloy composition increased, and when the alloy composition reached 19%, the hardness was equivalent to the base material. The average hardness value of the HAZ (35.8 HRC) was higher than that of the base metal (24.8 HRC). The tensile strength increased, and the percentage elongation after fracture decreased with increasing alloying composition from 9% to 19%. The impact absorbing energies were decreased as the alloying composition increased. Consequently, all the mechanical properties of rail ultranarrow gap welding were higher than those of the standard requirements of the rail flash welding. And the optimal alloying composition of flux band was 19%.